Employee’s Involvement Culture of Star Hotels in Pokhara - Dhakal, Daya Raj (Journal of Nepalese Business Studies, 2019)
Since the star hotels are directly relates to the both internal and external tourism it has important contributory role to the nation therefore smooth operation of the hotels is most. Looking to current performance of the hotels some of the hotels are in loss condition and therefore it becomes challenging issues for both hotel management and Nepal government. Several numbers of literatures have explained an employee involvement practice is one that affects organizational performance. Therefore this study attempts to explore existing situation of employee involvement culture and its association with performance of star hotels in Pokhara. Since Nepal government announced Nepal Visit Year 2020 this study is highly relevant. This study compare between hotels having involvement practices and non-involvement practices in association with their financial performance in Pokhara. The advantage of this research is broadly defined into three sets of variables as employee empowerment, team work and carer development that focus interrelationship with star hotel’s performance. The result revealed the hotels which have adopted employee involvement practices mostly get good financial result and vice versa. The result shows there is strong relationship between employee empowerment and team work practice with better financial result. Though previous literature explained career development is strong variable that supports performance, but in the Nepalese context this variable does not have significant impact. Hence, the study concludes that the management must give high priority to employee empowerment and team work and less priority to career development for better financial performance of the star hotels in Pokhara.